Pengaruh Terapi Inhalasi Eucalyptus Terhadap Bersihan Jalan Napas Pada Anak Dengan ISPA Di Wilayah Kerja Puskesmas Mamboro : Penelitian - Enjelina Sinaga; I Made Rio Dwijayanto; Agnes Erlita Distriani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Acute Respiratory Tract Infection (ARI) is one of the main causes of morbidity in children in Indonesia. One non-pharmacological intervention to help overcome airway clearance disorders is eucalyptus inhalation therapy. Based on observations at the Mamboro Community Health Center, most children with ARI have never received inhalation therapy regularly due to a lack of parental knowledge about its benefits. This study aims to determine the effect of eucalyptus inhalation therapy on airway clearance in children with ARI in the Mamboro Community Health Center working area. This study used a pre-experimental approach with a one-group pretest-posttest design. The sample consisted of 5 children with ARI obtained through a purposive sampling technique. The intervention was carried out for three days with eucalyptus inhalation therapy administered twice daily. Data were collected using an airway clearance observation sheet and analyzed using the Wilcoxon Signed Rank Test. The results showed a Z value of -2.060 with p = 0.039 (p < 0.05), which means there is a significant effect between eucalyptus inhalation therapy on improving airway clearance. Before the intervention, all respondents (100%) had poor airway clearance, while after the intervention all (100%) were in the good category. There is an effect of eucalyptus inhalation therapy on improving airway clearance in children with ARI in the working area of ​​the Mamboro Community Health Center.